2004
DOI: 10.1002/lt.20076
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial adjustment to orthotopic liver transplantation in 266 recipients

Abstract: Although the survival rate of patients undergoing orthotopic liver transplantation (OLT) is highly satisfactory, one of the most important objectives for liver transplantation teams at the present time is to achieve the best possible quality of life and psychosocial functioning for these patients after transplantation. We present the preliminary results of a study designed to determine which domains of psychosocial functioning are most affected in liver transplant recipients, and to examine the factors associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 23 publications
(33 reference statements)
4
44
1
2
Order By: Relevance
“…The differences were partially corrected after adjustment for educational level. A similar result was reported by Spanish investigators who reported that psychosocial adjustment after LT was rated higher in male compared to female recipients [27].…”
Section: Gender Differencessupporting
confidence: 89%
“…The differences were partially corrected after adjustment for educational level. A similar result was reported by Spanish investigators who reported that psychosocial adjustment after LT was rated higher in male compared to female recipients [27].…”
Section: Gender Differencessupporting
confidence: 89%
“…The differences were partially corrected after adjustment for educational level. A similar result was reported by Spanish investigators who reported that psychosocial adjustment after LTx was reported higher in males compared to female recipients (Blanch et al, 2004). Similarly, in research by Kotarska et al HRQOL was significantly worse in female patients in the majority of the SF-36 domains (Kotarska et al, 2014).…”
Section: Gender Differencessupporting
confidence: 84%
“…There are few, if any, studies of sexual health in the liver transplant literature worldwide, and we are unaware of any specific studies of this subject matter conducted in North America. A recent study 5 emphasizes the need for specific socioculturally generalizable studies. This study, conducted in Barcelona, included sexual health, but only as a domain within a larger psychosocial study using the Psychosocial Adjustments to Illness Scale.…”
Section: Discussionmentioning
confidence: 99%